Synthesis and tribocorrosion performances of multilayer (Ta/ZrN) n coatings - Beliardouh, Nasser Eddine; Ramoul, Chems Eddine; Nouveau, Corinne; Kaleli, Emrullah Hakan; Montagne, Alex (ELSEVIER SCIENCE SA, 2022)
Multilayer thin coatings (similar to 3 mu m in thickness) were deposited using reactive radio frequency magnetron sputtering on Ti-6Al-4 V substrate for biomaterial applications. Films are a combination of hard zirconium nitride with pure tantalum, used to manage interfacial stress and to avoid crack growth. Alternating hard/ductile material is a biomimetic design inspired by nature (nacre-inspired materials). Tribocorrosion tests were performed in Hank's solution at 37 degrees C, under open circuit potential by using a ball-on-disk reciprocating tribometer. A tendency to high resistance against corrosion was found for all the samples. Coatings with a top 100 nm thick ZrN layer showed more noble potential as well as a reduction of both the friction coefficient and the wear rate during the sliding phase. The principal wear mechanism is related to a tribocorrosion layer formation.
Keywords: Multilayer coating, Biomaterial, Tribocorrosion; Zirconium nitride; Magnetron sputtering; MAGNETRON; CORROSION; HARDNESS; DESIGN; SYSTEM; Materials Science; Physics